An overview of the principles of jurisprudence vis-a-vis legal maxims - Yahaya, Mohammad Zaini; Samsudin1, Muhammad Adib; Laluddin, Hayatullah (Canadian Center of Science and Education, 2014)
The Principles of Jurisprudence (Usul al-Fiqh) is a well-known science in the field of Shari’ah. Almost all institutions in Malaysia offering Islamic Studies in the field of Shari’ah make The Principles of Jurisprudence as compulsory course that must be taken by each candidate. This is due to the Principles of Jurisprudence dealing with crucial matters such as al-Dalil al-Ijmali (Comprehensive Proof), istinbat (derivation of rulings from nas (text) and debates related to ijtihad (the exertion of the utmost effort by a trained jurist). This study using both descriptive and analytical methods concludes that the Science of the Principles of Jurisprudence is extremely important for it equip the researcher with a clearer and deeper understanding of the Arabic speech rather than its linguistic sense and superficial meaning. Hence, the Principles of Jurisprudence is an absolute requirement for proper understanding of the Shari’ah, hence, derivation of rulings.